Interferons and Toxoplasma gondii shape PD-L1 regulation in retinal barrier cells: the critical role of proteases - Geiller, Benjamin; Cevallos, Camila; Tsybenko, Iuliia; Arnoux, Lydia; Felder-Schmittbuhl, Marie-Paule; Pfaff, Alexander W. (Frontiers in Immunology, 2025)
IntroductionThe apicomplexan parasite Toxoplasma gondii establishes chronic infection in the central nervous system, including the retina, causing ocular toxoplasmosis (OT). This persistence relies on a fine balance between inflammatory and immunomodulatory mechanisms, especially in the immune-privileged ocular environment. We previously described the immunologic interactions between retinal cells, and particularly the roles of type I and III interferons. In this study, we investigated the regulatory dynamics of PD-L1, a central immunomodulatory receptor on immune cells.MethodsWe first investigated the mechanisms of PD-L1 regulation and the roles of type I and III interferons in an in vitro T. gondii infection model using mono- and co-culture systems of human microglia, astrocytes, and Müller cells. We also assessed PD-L1 expression in an outer blood-retina barrier model (oBRB) of differentiated retinal pigmented epithelial (RPE) cells. Additionally, we looked at retinal cell activation, PD-L1 expression and the roles of these interferons in a mouse model of OT.ResultsOur findings reveal new roles for type I and III interferons in regulating glial cell activation and PD-L1 expression in RPE, Müller, astrocytes and microglial cells. Notably, Müller cells, the most abundant glial cells in the retina, showed the highest baseline PD-L1 expression at both the mRNA and protein levels, and responded robustly to interferon stimulation. This points to a more prominent immunoregulatory role for Müller cells in the retina than previously recognized. Furthermore, we identified a parasite protease-dependent mechanism that reduces PD-L1 expression in our in vitro oBRB model potentially contributing to immune evasion and inflammation during OT. Finally, in a murine model of OT, we demonstrated that PD-L1 expression reached its peak on day 7 post-infection and that interferon neutralization plays a crucial role in regulating both PD-L1 expression and glial activation.DiscussionThe parasite T. gondii orchestrates the IFN type I and III dependent retinal immune interaction and downregulates PD-L1 in the oBRB by a protease-dependent mechanism, potentially contributing to immune evasion and inflammation in retinal infection. Our results can pave the way to fully elucidate retinal immune networks and PD-L1 regulation mechanisms, offering potential targets for therapeutic interventions in OT and other retinal inflammatory diseases.